Istihalah contention in halal food ingredients - H., Ab. Rahim; Hadijah, Ahmad; Mohd Hairul, Ab. Rahim (Universiti Malaysia Pahang, 2023)
Modern food ingredients nowadays vary and more complex compared with previous decade so they come in different forms and content. They were produced with advanced technology that involved modification and changing in chemical, biological, and physical properties of food which aligned with the Istihalah concept. However, the issue becomes debatable among Muslim consumers when these beneficial food ingredients; protease enzymes and gelatin are made from non-halal sources which are blood and pork (khinzir). However, when referring to Istihalah, two different thoughts from Islamic jurists (ulama), Islamic scholars, and sects (Mazhab) were discovered. This contention might be escalated and become a misunderstanding among Muslims if there is no clarification made with the incorporation of Islamic guidance together with the science and technology explanation. Therefore, this paper will highlight the Istihalah principles in fiqh and Islamic Jurisprudence (Usul al-fiqh), a different point of view regarding Istihalah from Islamic jurists (ulama), sects (Mazhab), and Islamic Scholars, and the applications of Istihalah towards controversial food ingredients with support from latest science and technology studies. The expectation for this paper is to give a better understanding of Istihalah in Islamic perspectives proved by scientific foundation.